Clinical Profile And Survival Outcomes in Pediatric Germ Cell Tumors: Single Centre Experience - Latif, Ayesha; Ghafoor, Tariq; Hira, Benish; Siddique, Abdul Wahab; Manzoor, Rabiha; Naz, Shaista (Journal of Postgraduate Medical Institute, 2024)
Objective: This study was designed to assess the clinical features and survival outcomes of pediatric Germ cell tumors (GCTs) in our center. Materials and Methods: All newly diagnosed cases of GCTs in the Pediatric Oncology Department, Combined Military Hospital, Rawalpindi, between 1st January 2012 and 31st December 2023 were evaluated prospectively. Results: During the study period, 100 cases were treated for Germ Cell tumors. The cases with central nervous system GCTs, those who relapsed after receiving initial treatment at another institute, and those who lost to follow-up were excluded from this study The data of the remaining 86 cases was analyzed. The median age of the patients at presentation was 24 months (IQR: 15 to 66). The male-to-female ratio was 1.5:1. The most common symptom at presentation in males was scrotal swelling (68.4%), while in females, it was abdominal pain (55.1%). The most common anatomic site at presentation was gonadal n=57 (66.3% with 46.5% cases in the testis and 19.8% in the ovaries). Yolk sac tumor was the commonest type in 51(59.3%), followed by teratoma in 17(19.8%). The disease was metastatic in 29(33.7%) cases, and the most frequent site of metastasis was pulmonary 44.8%. The most common stage at presentation according to COG staging is stage 1(39.5%), followed by stage 4 (32.6%), and upon applying MaGIC risk group classification, Standard Risk 1 was the most common type, followed by Low-Risk type in 60.5% and 36% cases respectively. Serum Tumor Markers (STMs), alpha-FP, and beta-HCG were measured in all cases, and alpha-FP value was raised in 77 (89.5%) cases, whereas beta-HCG was high in 5 cases (5.81%). The Overall Survival (OS) and Disease-Free Survival (DFS) in our study was 90.7%. Conclusion: The clinical profile of GCTs in our study population is similar to those reported in other Asian and European studies. Our analysis points out age as the most critical determinant in the prognosis of pediatric GCT. Although Factors like serum AFP greater than 10,000 ng/ml and metastatic disease were associated with poor prognosis, we could not prove statistical significance due to the limited size of our study population. Therefore, multicentre prospective collaborative research is needed to ensure early diagnosis and adapt more effective treatment strategies for advanced cases.